State Policy, Sharia Principles, and Institutional Transformation in Kuwaiti Islamic Higher Education - Al Ajmi, Bader Khaled Marzouq; Al Rashidi, Yousef Hamad Dhafer (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2026)
This article examines the transformation of Islamic higher education in Kuwait through the interaction of state policy, Sharia principles, privatization, digital modernization, and global higher education models. Using a qualitative library-based approach, combined with policy analysis and an integrative literature review, the study analyzes how Kuwaiti Islamic higher education has moved beyond a primarily religious-knowledge orientation toward a more complex institutional model shaped by governance reform, quality assurance, internationalization, and technological innovation. The findings show that Kuwait’s higher education transformation is neither a purely secular modernization project nor a simple continuation of religious tradition. Rather, it is a negotiated process in which state regulation, Sharia-based ethics, private higher education, digital learning, and global academic standards continuously interact. Sharia principles influence curriculum design, institutional governance, financial management, and ethical accountability, while state policy provides the regulatory framework for privatization, accreditation, and modernization. The article contributes by proposing a Hybrid Policy-Sharia Transformation Framework to understand Islamic higher education reform in Kuwait. This framework emphasizes regulatory alignment, Sharia-based governance, pedagogical modernization, participatory reform, and integrated quality assurance as key dimensions for future institutional development.